2019
DOI: 10.1002/jcp.28142
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐505 negatively regulates HMGB1 to suppress cell proliferation in renal cell carcinoma

Abstract: microRNAs have been recognized to regulate a wide range of biology of renal cell carcinoma (RCC). Although miR‐505 has been reported to play as a suppressor in several human tumors, the physiological function of miR‐505 in RCC still remain unknown. Therefore, the role of miR‐505 and relevant regulatory mechanisms were investigated in RCC in this study. Quantitative real‐time polymerase chain reaction was conducted to detect the expression of miR‐505 and high mobility group box 1 (HMGB1) in both RCC tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…In the current work, we observed an upregulation of miR‐205‐3p and miR‐505‐3p in HCD cells exposed to HK2 EVs (Figure 3C). Our data are in line with previous studies reporting the presence of both miRNAs in HK2 cells 59‐61 . Furthermore, miR‐205 was also described in human UEVs 20 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current work, we observed an upregulation of miR‐205‐3p and miR‐505‐3p in HCD cells exposed to HK2 EVs (Figure 3C). Our data are in line with previous studies reporting the presence of both miRNAs in HK2 cells 59‐61 . Furthermore, miR‐205 was also described in human UEVs 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with previous studies reporting the presence of both miRNAs in HK2 cells. [59][60][61] Furthermore, miR-205 was also described in human UEVs. 20 Since both miRNAs target ENTPD1 mRNA, their upregulation may explain ENTPD1 downregulation, whereby the transfer of the miRNAs from HK2 to HCD cells via EVs appears as a likely mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It was turned out by Chen et al that miR-505 was overproduced in EC cells, leading to the reduction of TGF-α, MMP-2 and MMP-9, but enforced the productions of Bax and cleaved-PARP [26]. Additionally, Zhong et al revealed that miR-505 functioned as a tumor suppressor in RCC by down-regulating HMGB1 [11]. Out of question, an ingenious phenomenon was obtained in this present investigation.…”
Section: Discussionsupporting
confidence: 49%
“…Dang et al found that miR-505 had some connection with GC cell proliferation and invasion [10]. Zhong et al pointed out that miR-505 functioned as a tumor suppressor in RCC by down-regulating high mobility group box-1 protein (HMGB1) [11]. What's interesting, circRNAs always exert dedicated regulatory functions in carcinoma via acting as a sponge of the miRNAs [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the abnormal expression of miR in tumors has been observed in a number of studies; consequently, miR has been suggested as a tumor target [8][9][10] given its role in supporting the functions of cancer genes and anti-oncogenes. Being a member of miR, the possible role of miR-505 as an anti-oncogene has been revealed in several types of tumors in recent years [11,12]. Some studies have shown that miR-505 can promote the chemoresistance of mammary cancer cells by inhibiting cell proliferation through apoptosis induction and its expression is related to established biomarkers for the prognosis of mammary cancer [13].…”
mentioning
confidence: 99%